KESADARAN ORANG TUA BUDDHIS PADA PENDIDIKAN SEKS UNTUK ANAK USIA SD DI KABUPATEN SEMARANG - Sukodoyo (Jurnal Penjaminan Mutu, 2024)
The background of this research is the phenomenon of sex education among Buddhist parents. The objective of this research is to describe the awareness of Buddhist parents in Getasan District, Semarang Regency, concerning sex education for elementary school-age children. This research uses a qualitative approach with the type of case study research. The subjects consist of Buddhist parents in Getasan District, Semarang Regency, who had elementary school-age children aged 6–12 years. The method of data collection is done by using interviews, observation, and documentation. Data analysis is carried out through the stages of data reduction, data display, and verification, as well as drawing conclusions. The importance of sex education for elementary school-age children encompasses aspects such as education based on learning outcomes and parental awareness, understanding grounded in explanations of the anatomy and reproductive organs of both genders, knowledge based on the impact of sexual harassment and violence, the inculcation of love and adherence to five moral rules in children, and measures for preventing and addressing sexual violence; (2) Influential factors on Buddhist parents concerning sex education for elementary school-age children include parental knowledge and child-rearing approaches, parental role modeling, family financial status, peer influence, and community dynamics; (3) The role of Buddhist parents in sex education for elementary school-age children involves guiding children to perform virtuous deeds, being a child’s friends, serving as role models, explaining methods to prevent violence against children through the implementation of the five precepts (moral code of conduct) and shame of evil and fear of its result, loving-kindness and the noble eightfold path, as well as highlighting the significance of Buddhist values for the well-being of children.